MANAJEMEN ZAKAT PRODUKTIF - Hadi, Solikhul (UIN Sunan Kudus, 2016)
This study aims to describe the mechanism of productive zakat management. The approach in this research is qualitative with a descriptive method. Thus, this research is expected to be able to contribute to finding professional zakat management solutions in Indonesia. The results of the study describe that to achieve the empowerment of productive zakat management, four things are needed. First; zakat management planning, includes 1) institutional strategic planning, taking into account, among others, the following: the results to be achieved, what will be done, time, priority scale, and capital. 2). Planning of institutional goals to give birth to the vision and mission of a zakat institution/organization. Second; the organization of zakat management, taking into account: the existence of goals to be achieved, the determination and grouping of work, the authority and responsibility, the relationship with each other, and the determination of the people who will carry out the work or tasks assigned to them. Third; implementation in the collection and distribution of zakat. There are three strategies in the implementation of zakat collection, namely: the formation of a zakat collection unit, opening a zakat receiving counter, and opening a bank. As for the implementation of productive zakat distribution, it can be categorized in several ways, namely: conventional productive and creative production. Fourth; Supervision of zakat management. This process is to ensure that organizational and management objectives are achieved. This relates to ways to make activities according to previously planned in order to measure the achievement of results. Regular supervision starts from planning, organizing, and implementing.